The Impact of Flexible Working on Employee Performance in a Hybrid Work System - Arananda Putri Sari; Ifan Rofiqoh (Oikonomia : Journal of Management Economics and Accounting, 2026)
The shift toward hybrid work systems has positioned flexible working arrangements as a central strategy in modern organizational design. This study examines how Flexible Working Arrangements influence Employee Performance within a hybrid work context through the mediating role of Organizational and Technological Resources. A quantitative explanatory approach was employed using survey data collected from employees who had experienced hybrid work for at least six months. The data were analyzed using SEM-PLS to test the relationships among flexibility, resources, and performance. The results indicate that Flexible Working Arrangements have a positive and significant direct effect on Employee Performance and a stronger effect on Organizational and Technological Resources, which in turn significantly improve performance. The mediation analysis confirms that resources partially mediate the relationship between flexibility and performance. These findings suggest that autonomy, work–life balance, and engagement derived from flexible working contribute to improved task, contextual, and adaptive performance, but the effectiveness of flexibility depends heavily on supportive organizational practices and technological readiness. The study concludes that performance gains in hybrid systems are achieved when flexible policies are embedded within a resource-supported work environment.